2020
DOI: 10.2139/ssrn.3645468
|View full text |Cite
|
Sign up to set email alerts
|

Wage Losses and Inequality in Developing Countries: Labor Market and Distributional Consequences of COVID-19 Lockdowns in Turkey

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition, the fact that the fortunes of billionaires affiliated to digital giants and large pharmaceutical companies increase more and more as the stock prices increase is one of the determining factors in the deepening of inequalities. Duman (2020) suggested that isolation policies due to Covid-19 can increase wage inequality depending on supply shocks in Turkey. Similarly, Bayar et al (2020), in their study of labor market indicators in Turkey due to Covid-19, reached the findings that low-income groups lost more income than high-income groups.…”
Section: Literaturementioning
confidence: 99%
“…In addition, the fact that the fortunes of billionaires affiliated to digital giants and large pharmaceutical companies increase more and more as the stock prices increase is one of the determining factors in the deepening of inequalities. Duman (2020) suggested that isolation policies due to Covid-19 can increase wage inequality depending on supply shocks in Turkey. Similarly, Bayar et al (2020), in their study of labor market indicators in Turkey due to Covid-19, reached the findings that low-income groups lost more income than high-income groups.…”
Section: Literaturementioning
confidence: 99%